Molecular imaging of viral pathogenesis and opportunities for the future - Brianna Kelly; Jeanette E. Boudreau; Steven Beyea; Kimberly Brewer (npj Imaging)
Abstract Molecular imaging is used in clinical and research settings. Since tools to study viral pathogenesis longitudinally and systemically are limited, molecular imaging is an attractive and largely unexplored tool. This review discusses molecular imaging probes and techniques for studying viruses, particularly those currently used in oncology that are applicable to virology. Expanding the repertoire of probes to better detect viral disease may make imaging even more valuable in (pre-)clinical settings.